Effect of Axial Load on the Seismic Performance of Steel Reinforced Concrete Beam-Column Joint - Iranata, Data; Suswanto, Budi; Amalia, Aniendhita Rizki; Tajunnisa, Yuyun; Septiarsilia, Yanisfa (Civil Engineering Journal, 2025)
Steel-reinforced concrete (SRC) provides numerous advantages, such as enhanced energy dissipation, ductility, stiffness, and strength, particularly in seismic performance. Several studies on the effect of axial loads on columns found that axial loads have an insignificant influence on column capacity, though they influence long-term performance. Beam-column joint elements are among the critical components that determine the seismic behavior of a structure. Inaccurate design of these joints can lead to fatal structural damage, potentially causing structural collapse. This study aimed to perform a numerical analysis of various joint configurations under cyclic and axial loads to identify models with the best seismic performance that consisted of four models using different SRC length parameters. The research used nonlinear finite element methods with the ABAQUS software, which enables detailed simulations of joint behavior, including predictions of failure mechanisms that are difficult to observe in experimental testing. The results of the analysis showed that the CS-02 model demonstrated the best seismic performance. Axial load increased the capacity in all models, improved energy dissipation in the RC model, slightly reduced dissipation in CS models, and caused different rotational behavior across models.